MONOPOLI KERAJAAN (MOJA) UNTUK MENINGKATKAN KETERAMPILAN PROSES PADA MATERI HINDU BUDHA DI KELAS IV SEKOLAH DASAR - Sekar Arum Mulyaning Tyas; Iin Purnamasari; Wawan Priyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Learning media is important in the era of industrial revolution 4.0. At SD Negeri Gumelem IPAS subjects combine Natural and Social Sciences to increase the relevance of the material to real life and develop critical skills, communication, collaboration and innovation. The research and development (R&D) method was used to create innovative learning media. The development of monopoly game as a media for grade IV students helps to improve motivation and learning outcomes. At SD Negeri Gumelem and SD Negeri 02 Siwalan, the results showed an increase in the average score from 59.16 in the pre-test to 76.94 in the post-test. MOJA learning media was validated by experts with a score of 85.71% and 96.71%, categorized as "Very Feasible". The trial on grade IV students showed significant improvement. This media is effective and recommended to support the teaching and learning process, especially the material of the Hindu Buddhist Kingdom.